MITRAC15/COA1 promotes mitochondrial translation in a ND2 ribosome–nascent chain complex. (13th November 2019) - Wang, Cong; Richter‐Dennerlein, Ricarda; Pacheu‐Grau, David; Liu, Fan; Zhu, Ying; Dennerlein, Sven; Rehling, Peter
Abstract: The mitochondrial genome encodes for thirteen core subunits of the oxidative phosphorylation system. These proteins assemble with imported proteins in a modular manner into stoichiometric enzyme complexes. Assembly factors assist in these biogenesis processes by providing co‐factors or stabilizing transient assembly stages. However, how expression of the mitochondrial‐encoded subunits is regulated to match the availability of nuclear‐encoded subunits is still unresolved. Here, we address the function of MITRAC15/COA1, a protein that participates in complex I biogenesis and complex IV biogenesis. Our analyses of a MITRAC15 knockout mutant reveal that MITRAC15 is required for translation of the mitochondrial‐encoded complex I subunit ND2. We find that MITRAC15 is a constituent of a ribosome–nascent chain complex during ND2 translation. Chemical crosslinking analyses demonstrate that binding of the ND2‐specific assembly factor ACAD9 to the ND2 polypeptide occurs at the C‐terminus and thus downstream of MITRAC15. Our analyses demonstrate that expression of the founder subunit ND2 of complex I undergoes regulation. Moreover, a ribosome–nascent chain complex with MITRAC15 is at the heart of this process. Synopsis: The mitochondrial genome encodes core subunits of the oxidative phosphorylation system. This study shows that MITRAC15 promotes the translation of the ND2 subunit of complex I as part of a ribosome‐nascent chain complex. MITRAC15 is required for complex I assembly. Loss of MITRAC15 affects translation of the mitochondrial‐encoded subunit ND2. MITRAC15 associates with nascent ND2 during translation. Abstract : The mitochondrial genome encodes core subunits of the oxidative phosphorylation system. This study shows that MITRAC15 promotes the translation of the ND2 subunit of complex I as part of a ribosome‐nascent chain complex.